371 Panorama of Castries, St. Lucia - (:unkn) unknown (My University, 2022)
Aerial view of buildings in the town. Architectural features of buildings and rooftops are visible. mountains and a seascape are visible in the background. On the other side of the card, a seascape with the mountains in the background is featured.
Landscape; Sephia tone; 6" x 8 1/4" (print mounted on card)
Keywords: Aerial views; Cities and towns; Hip roofs; Roofs; Architecture; Buildings; Cityscapes; Architectural elements; Mountains